Knowledge Management Strategies In The Telecommunication Industry in Ghana: A Systematic Review - Lawrence Akosen; Nasir Koranteng Asiedu; De-Graft Johnson Dei (Journal of Business and Management Review, 2022)
Knowledge management techniques in Ghana's telecommunications industry have become critical in the previous few years. It has acted as a catalyst in altering telecoms' competitive advantage as the major industry in African countries' development agendas. The study adopted the systematic review approach in evaluating literature and discussing and presenting findings. The findings revealed that leadership directions are vital to the knowledge management strategic approach in the telecommunication industry in Ghana. Furthermore, the creation of the Chief Knowledge Officer (CKO) in the industry has promoted the establishment and set of knowledge management priorities for competitive advantage. The study suggests that knowledge management strategies have global appeal influencing the local drive for success and so should be given the needed attention by industry players.